2008
DOI: 10.1089/fpd.2008.0123
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Invasive Isolates ofListeria monocytogenesin Sweden 1986–2007

Abstract: Since 1986, 68% of the Listeria monocytogenes isolates from human cases of invasive listeriosis in Sweden are available for retrospective studies. The aim of the present study was to characterize 601 human invasive isolates of L. monocytogenes in Sweden from 1986 to 2007 by using serotyping and pulsed-field gel electrophoresis. Since 1996, serovar 4b was permanently reduced to the second or third most common serovar in human cases in Sweden. During the latter period, 2000-2007, only 13% belonged to serovar 4b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 35 publications
2
33
0
3
Order By: Relevance
“…In this study, it was found that the isolates of L. monocytogenes serotypes 4b, 1/2a and 1/2b were strongly correlated within the same serotypes and, in some cases, between the different serotypes, indicating a common origin. The same results were observed by other authors (PARIHAR, et al, 2008).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, it was found that the isolates of L. monocytogenes serotypes 4b, 1/2a and 1/2b were strongly correlated within the same serotypes and, in some cases, between the different serotypes, indicating a common origin. The same results were observed by other authors (PARIHAR, et al, 2008).…”
Section: Resultssupporting
confidence: 92%
“…There is a discussion about the relationship of the origin of two lineages found in L. monocytogenes, the lineage I represented by serovars 1/2b and 4b, and the lineage II represented by serovars 1/2a and 1/2c (PARIHAR et al, 2008). According to NIGHTINGALE et al (2005), lineage I comprises the strains which have adapted to the human host, while lineage II comprises the strains which have been environmentally adapted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While a few studies (Hong et al, 2007;Jeffers et al, 2001;Kiss et al, 2006) have shown that lineage I isolates are also overrepresented among sporadic cases of human listeriosis (e.g., as compared to their prevalence among food isolates), this trend does not seem to be consistent and the association between lineages and human listeriosis cases may vary by region. In particular lineage II serotype 1/2a strains appear to be more common among human listeriosis cases in Northern Europe [e.g., in Finland (Lukinmaa et al, 2003) and Sweden (Parihar et al, 2008)], Fig. 2.…”
Section: Distribution Of L Monocytogenes Lineages Among Human Isolatesmentioning
confidence: 99%
“…Studies in a number of countries indicate that lineage I strains are overrepresented among human cases compared to lineage II strains, even though lineage II strains still frequently cause disease in humans (9,11). Nevertheless, overrepresentation of lineage I strains among human cases has not been observed in some countries, such as Finland (12) and Sweden (13). In many studies, lineage II seems to be the most common lineage among isolates from foods and food-related environments, such as food processing plants (14), posing the question of why these lineage II isolates are not more frequently found among human clinical cases.…”
mentioning
confidence: 99%